2013
DOI: 10.4322/polimeros.2013.025
|View full text |Cite
|
Sign up to set email alerts
|

The influence of screw configurations and feed mode on the dispersion of organoclay on PP

Abstract: The design of the screw configuration as well as the screw speed, the residence time, the feeder type, and the temperature has a large effect on the dispersion of the clay into the matrix and, consequently, on the mechanical and thermal properties of the polymeric matrix. The objective of the present work was to evaluate the influence of two different screw configurations (left-handed elements) and the feed type (hopper or side feeder) on the dispersion of 5 wt% Cloisite 20A into the PP matrix without the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Mauler and co-workers 32 and Modesti et al. 33 pointed out that thermal stability of PP matrix was improved independent on the profile screw configuration and feeder type for PP/organoclay nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mauler and co-workers 32 and Modesti et al. 33 pointed out that thermal stability of PP matrix was improved independent on the profile screw configuration and feeder type for PP/organoclay nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…About crystallinity degree (X c ), only the nanocomposite processed at 90 r/min showed some decreasing. Mauler and his co-workers 32 reported that different screw configurations and feed modes did not affected T m but the presence of organoclay promotes a slight increasing on T c and decreasing of PP degree of crystallinity. Modesti et al .…”
Section: Calorimetric Propertiesmentioning
confidence: 96%
“…Modesti et al 46 reported an increase of PP degree of crystallinity in composites filled with montmorillonite. Santos et al 47 registered no variation of T m and X c in their work on the influence of screw configurations and feed mode on the dispersion of organoclay into PP matrix. We devote our results as nucleation effect of the zirconium phosphate through the transcrystallization (heterogeneous nucleation on the highly crystalline matter).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 96%
“…The amide groups of polyamide are very polar, and hydrogen bonds can form between them. Because of these, and because the polyamide backbone is so regular and symmetrical, polyamides are often crystalline, and make very good fibers (15)(16) . Mixing and dispersing nanosized particles in polymer matrices provide the resulting materials with a variety of properties which are simply not available for bulk composites with high filler loading.…”
mentioning
confidence: 99%